EFICIÊNCIA DA INOCULAÇÃO COM AZOSPIRILLUM BRASILENSE ASSOCIADA A ADUBAÇÃO ORGANOMINERAL NA CULTURA DO AMENDOIM - Abel dos Santos , Benjamin; Gabriel de Souza Ricardo , Victor; Henrique de Oliveira Gaiola , Lucas; Rafael Simbre Barbosa , Bruno; Melo Machado , Cauã; Zoz , Tiago (ANAIS DO ENIC, 2026)
-